Evaluation of Malthus 128H microbiological growth analyser for detecting significant bacteriuria. Issue 8 (August 1985) - Smith, T K; Eggington, R; Pease, A A; Harris, D M; Spencer, R C
Abstract : In a pilot study a prototype Malthus 128H microbiological growth analyser was used to study the growth of six commonly encountered urinary pathogens in a range of five different laboratory media. No single medium had been able to show acceptable conductance changes for all bacteria within five hours. Subsequently, the Malthus system, with fastidious anaerobe broth as the culture medium, was used to screen 500 consecutive clinical specimens of urine for significant bacteriuria. After two and a half hours the Malthus system detected 32 out of the 40 true positives and eight of the 44 contaminated urines. Increasing the detection time to five hours permitted the recognition of 39 true positives and 37 contaminated urines.